Bertahan Hidup dalam Bencana: Peran Perempuan Minang Pasca Gempa Bumi 2009 di Padang Sumatera Barat - Putri, Selfi Mahat; Fitri Ramadani, Ana; Amelia Furqon, Rizky; Zulqaiyyim, Zulqaiyyim (Jurnal Pattingalloang, 2024)
Padang City, West Sumatra is one of the areas that is prone to earthquake and tsunami disasters. One of the biggest disasters that hit this city was the earthquake of September 30, 2009, which had a wide impact on the people of West Sumatra, especially Padang City. This study aims to analyze the role of Minang women in post-earthquake recovery in 2009 in Padang, West Sumatra. This study uses historical methods with data sources from literature studies and interviews. The results of this study show that Minang women are not only vulnerable victims of disasters, but also agents of change in the family and society. Minang women became the backbone of the family when men (husbands) lost their jobs or income sources due to disasters. Minang women also play an active role in earning a living, helping the rehabilitation and reconstruction process.Keywords: Earthquake, Padang, Role, Women, Minang